2003
DOI: 10.1073/pnas.1633579100
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide negatively regulates mammalian adult neurogenesis

Abstract: Neural progenitor cells are widespread throughout the adult central nervous system but only give rise to neurons in specific loci. Negative regulators of neurogenesis have therefore been postulated, but none have yet been identified as subserving a significant role in the adult brain. Here we report that nitric oxide (NO) acts as an important negative regulator of cell proliferation in the adult mammalian brain. We used two independent approaches to examine the function of NO in adult neurogenesis. In a pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
261
1
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(291 citation statements)
references
References 48 publications
22
261
1
4
Order By: Relevance
“…The number of newly generated cells in the olfactory bulb and dentate gyrus also is enhanced significantly in null mutant mice lacking neuronal NOS activity (Packer et al, 2003). These studies implicate nitric oxide as a negative regulator of cell proliferation and a positive promoter of neuronal fate determination in neurogenic regions of the adult brain.…”
Section: Neurotransmitters and Other Factorsmentioning
confidence: 82%
See 1 more Smart Citation
“…The number of newly generated cells in the olfactory bulb and dentate gyrus also is enhanced significantly in null mutant mice lacking neuronal NOS activity (Packer et al, 2003). These studies implicate nitric oxide as a negative regulator of cell proliferation and a positive promoter of neuronal fate determination in neurogenic regions of the adult brain.…”
Section: Neurotransmitters and Other Factorsmentioning
confidence: 82%
“…Nitric oxide synthase (NOS) inhibitors increase SVZ proliferation and delay neuronal maturation of SVZ precursor progeny that migrate to the olfactory bulb (Cheng et al, 2003;Packer et al, 2003;MorenoLopez et al, 2004). The number of newly generated cells in the olfactory bulb and dentate gyrus also is enhanced significantly in null mutant mice lacking neuronal NOS activity (Packer et al, 2003).…”
Section: Neurotransmitters and Other Factorsmentioning
confidence: 99%
“…Nitric oxide exerts a dual effect on neurogenesis: While nNOS-derived NO decreases neurogenesis (Packer et al, 2003;Moreno-Lopez et al, 2004;Zhu et al, 2006), NO produced by endothelial (Reif et al, 2004) or inducible (Luo et al, 2007;Bechade et al, 2011) NOS seems to stimulate it.…”
Section: Nitric Oxide-physiologymentioning
confidence: 99%
“…Treatment with iNOS inhibitor aminoguanidine prevented postischemic neurogenesis ; the phenomenon could not be detected in iNOS null mice, either . Nitric oxide produced by nNOS exerts negative effects on neurogenesis (Packer et al, 2003;Moreno-Lopez et al, 2004;Luo et al, 2007), nNOS inhibition has been shown to increase neurogenesis after experimental ischemia (Sun et al, 2005). Neuronal NOS and iNOS therefore seem to have opposite roles in postischemic neurogenesis.…”
Section: Nitric Oxide-pathophysiology In Strokementioning
confidence: 99%
“…In contrast, iNOS is induced when macrophages and other cells are activated by inflammatory mediators and, unlike the constitutively expressed types, can be expressed at relatively high levels [13]. Nitric oxide has been shown to be involved in the differentiation, proliferation and apoptosis of neuronal cells [14][15][16]; the effect of nitric oxide is either physiological or cytotoxic, depending on its level. For example, a low level of nitric oxide has antioxidant and anti-apoptotic properties and plays an important role in normal development.…”
Section: Introductionmentioning
confidence: 99%